Investigating mathematical conversation in remote learning of mathematics during the covid-19 pandemic - Ayunda Sri Wahyuningrum; Titin Latifah (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2020)
Remote learning that must be carried out by schools in Indonesia during the COVID-19 pandemic was a challenge for most teachers. This study aimed to investigate mathematical conversations maintained by the teachers in remote learning of mathematics during the COVID-19 pandemic. It was a descriptive qualitative study that was analyzed based on school time during the pandemic, online teaching platforms used, the way the teachers carry out remote learning of mathematics, and how the teachers and the students interact. The data were collected from three mathematics teachers and eight students in a public senior high school in Bekasi District, Indonesia. They were interviewed by phone, and then the results of the interview were complemented by several captures of the students' conversations when learning mathematics via WhatsApp. This study revealed that remote learning of mathematics was still dominated by a rigid or less interactive learning environment, which could be seen from how the teachers gave mathematics problems, questions, and instructions, as well as how they responded to student questioning.